PERAN MEDIASI GOOD CORPORATE GOVERNANCE (GCG) DALAM MEMPENGARUHI KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN - Sukrin Sukrin (JEP (Jurnal Ekonomi Pembangunan), 2020)
The purpose of this study were to examine and explain the influence financial performance to good corporate governance (GCG) and the value of the company, to examine and explain the influencegood corporate governance (GCG) tothe value of the company, to examine and explain the influence good corporate governance (GCG) in mediating the relationship between the financial performance of the the value of the company. The design of the study is a quantitative research. The data used secondary data such as data based on time series (time series). Analysis of data usingsoftware Smart PLS version 3.0. The results showed that: Financial performance significantly influence the value of the company. The financial performance of no significant effect on good corporate governance (GCG). Good corporate governance (GCG) has no effect on the value of the company. The influence of the financial performance of the company's value mediated by good corporate governance (GCG) has no significant effect on firm value